Contractor prequalification for green buildings-evidence from Turkey - Gurgun, Asli Pelin; Koc, Kerim (EMERALD GROUP PUBLISHING LTD, 2020)
Purpose Competent contractors are one of the critical stakeholders to achieve targeted sustainability objectives in green building (GB) projects. Prior to contractor selection, prequalification is an important step, which requires contractors with certain capabilities in addition to traditional features. This study aims to develop a systematic and practical model for prequalification in GB projects using a multi-criteria decision-making (MCDM) approach by adopting the analytical hierarchy process (AHP). Design/methodology/approach The AHP model with 8 main criteria groups and 25 sub-criteria is structured based on literature review and professional opinions accompanied by a pilot study. Then, interviews with experts, who are experienced in the development and application phases of GB projects in Turkey, are arranged to collect judgements. The agreement levels between different groups of experts are analysed via Pearson's and Spearman's rank correlation coefficient. Model applicability is tested on six hypothetical contractors for practicality. Findings The results show that i) financial capabilities, ii) legal status and iii) sustainability groups are the top three main criteria, while i) compliance with schedule requirements of the client, ii) current legal status including suits, iii) negative litigation history records, iv) contractor's compliance capacity to client's sustainability checklist for the proposed project and v) sustainability with lower life cycle cost (durability, maintenance, constructability) are the top five sub-criteria. Originality/value There is a gap in the literature analysing contractor prequalification phase in GB projects. This study attempts to fill this lack provided with a practical evaluation tool.
Keywords: Green building; Prequalification; Construction industry; Decision making; AHP; MCDM; DECISION-SUPPORT-SYSTEM; MAKING MODEL; CONSTRUCTION; SELECTION; CRITERIA; SUSTAINABILITY; IMPACTS; RISKS; STATE; Engineering; Business & Economics